2022
DOI: 10.1038/s41598-022-10927-0
|View full text |Cite
|
Sign up to set email alerts
|

Extending UTAUT with national identity and fairness to understand user adoption of DCEP in China

Abstract: The introduction of digital currency electronic payment (DCEP) by the Central Bank of China is conducive to the central bank's timely grasp of macroeconomic dynamics and the internationalization of RMB. As DCEP is one of the first digital currencies issued by the central bank to be used on a large scale internationally, it is necessary to conduct research on its user adoption. Therefore, this research extends the unified theory of acceptance and use of technology (UTAUT) to explore factors affecting the adopti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 61 publications
1
9
0
Order By: Relevance
“…However, in online purchasing services, financial, product, security, time, and psychological risks negatively affect the intention to use (Ariffin, Mohan & Goh, 2018). Meanwhile, perceived risk affected the usage of digital currency electronic payment (Wu, An, Wang & Shin, 2022). These findings indicate that the higher the risk, the lower the intention to use digital payments again.…”
Section: Digital Payment Risks and The Impact Of Covid-19mentioning
confidence: 93%
“…However, in online purchasing services, financial, product, security, time, and psychological risks negatively affect the intention to use (Ariffin, Mohan & Goh, 2018). Meanwhile, perceived risk affected the usage of digital currency electronic payment (Wu, An, Wang & Shin, 2022). These findings indicate that the higher the risk, the lower the intention to use digital payments again.…”
Section: Digital Payment Risks and The Impact Of Covid-19mentioning
confidence: 93%
“…In global e-commerce and corporate payments, DCEP can exert the advantage of government support to ensure that the transaction process is more convenient and friendly (Wang et al 2022a , b ). Regarding promotions, users with a higher sense of national identity are more likely to use DCEP (Wu et al 2022 ). Owing to security concerns and economic benefits, users with less social experience tend to trust new payment tools (Ključnikov et al 2020 ), but CBDCs need to design their figures and enhance their popular identity to stimulate soft trust among users (Tronnier et al 2022 ; Radic et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Common factors influencing users’ switching behavior include quality, satisfaction, value, trust, commitment, price perception, alternative attitudes, social impacts, switching costs, previous switching behavior, and diversification tendencies (Kesharwani et al 2021 ; Li 2021 ; Rahman et al 2020 ; Rouibah et al 2021 ; Sampaio et al 2021 ; Shiau et al 2021 ; ZareRavasan and Krčál 2021 ). Digital currency and electronic payment research focusing on consumers’ choices of payment tools is increasing (Wu et al 2022 ). Previous studies have revealed the following two challenging steps in guiding payment behavior: (1) changing payment preferences and (2) the actual payment choice to match new payment preferences (van der Cruijsen and van der Horst 2019 ).…”
Section: Theoretical Backgroundsmentioning
confidence: 99%
“…They were rated on a seven-point Likert scale (1 strongly disagree, 7 strongly agree). Social Influence construct was measured using three items Based on Wu, An, Wang, and Shin (2022). My colleague suggested that I use live broadcast platforms.…”
Section: Methodsmentioning
confidence: 99%